Sacubitril-valsartan improves radial and longitudinal strain and ejection fraction in C57Bl/6 mice treated with doxorubicin through NLRP3 mediated pathways and reduction of cytokine storm. (4th February 2022) - Quagliariello, V; Buccolo, S; Iovine, M; Maurea, C; Rea, D; Barbieri, A; Maurea, N
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Ricerca Corrente grant, Ministero della Salute (it) Background: Doxorubicin-mediated adverse cardiovascular events are among the leading causes of morbidity and mortality in breast cancer patients. Sacubitril-valsartan (LCZ 696) is a combination drug, made up of neprilysin inhibitor sacubitril and angiotensin II receptor blocker valsartan, used for the treatment of heart failure in patients with a reduced ejection fraction. Hypothesis: we hypothesized that LCZ 696, administered during doxorubicin, could improve cardiac functions in preclinical models Methods:  C57Bl/6 mice were untreated (Sham, n = 6) or treated for 10 days with doxorubicin i.p at 2.17 mg/kg (DOXO, n = 6), LCZ-696 at 60 mg/kg (LCZ, n = 6) or doxorubicin combined to LCZ-696 (DOXO-LCZ, n = 6). Before and after treatments, ejection fraction (EF) and radial and longitudinal strain were analyzed through transthoracic echocardiography (Vevo 2100). After treatment, mice were sacrificed and cardiac tissues were treated for determination of NLRP3 inflammasome, Myd88, NF-kB and cytokines involved in heart failure and arrhythmias (IL-1α, IL-1β, IL-2, IL-4, IL-6, IL-10, IL-12, IL17-α, IL-18, IFN-γ, TNF-α, G-CSF, and GM-CSF). Results: LCZ 696 improved significantly the EF and prevented the reduction of radial and longitudinal strain after 10 days of treatment with doxorubicin. No significant differences were observed for IVS;d-D, LVID;d-D, LVPW;d-D, LV Mass, LV Vol; d, LV Vol;s between the experimental groups.  A reduced expression of NLRP3, MyD88 and NF-kB in cardiac tissues was seen in DOXO-LCZ group compared to DOXO mice (p < 0.001). Cardiac expression of IL-1β, IL-6, TNF-α, G-CSF and GM-CSF were significantly reduced (p < 0.001) after treatment with LCZ-696 indicating anti-inflammatory and cardioprotective properties. Conclusion: LCZ-696 improves cardiac functions in mice treated with doxorubicin. Biochemically, these effects are mediated by the downregulation of NLRP3 inflammasome-related pathways and cytokines involved in doxorubicin-mediated heart failure and cardiomyopathies.